Transient Serotonin Toxicity Evoked by Combination of Electroconvulsive Therapy and Fluoxetine - René Klysner; Birgitte Bjerg Bendsen; Maja Soon Hansen (Case Reports in Psychiatry)
The serotonin syndrome has been described only in rare instances for electroconvulsive therapy combined with an antidepressant medication. We describe a case of serotonin toxicity induced by electroconvulsive therapy in combination with fluoxetine.